Cetacean occurrence, habitat preferences and potential for cetacean–fishery interactions in Iberian Atlantic waters: results from cooperative research involving local stakeholders. Issue 1 (26th June 2014) - Goetz, Sabine; Read, Fiona L.; Ferreira, Marisa; Portela, Julio Martínez; Santos, Maria Begoña; Vingada, José; Siebert, Ursula; Marçalo, Ana; Santos, Jorge; Araújo, Hélder; Monteiro, Silvia; Caldas, Mara; et al.
Abstract Iberian Atlantic waters are heavily exploited by Spanish and Portuguese fisheries. Overlaps between fishery target species and cetacean diet, and between fishing grounds and cetacean foraging areas, can lead to cetacean–fishery interactions including bycatch mortality of cetaceans. The present study assesses cetacean distribution, habitat preferences and hotspots for cetacean–fishery interactions by using a cooperative research approach with stakeholder participation (fishers, fisheries observers, fisheries authorities, scientists), as well as the combination of different opportunistic data sources (interviews, on‐board observations). The usefulness of each data type is evaluated. The implications of results for the monitoring and mitigation of cetacean–fishery interactions are discussed. Generalized linear models and GIS maps were used to relate cetacean occurrence patterns to environmental variables (geographic area, water depth, coastal morphology) and to fishing activities (fishing grounds, fisheries target species). Common and bottlenose dolphins were the most frequently sighted species, the former in waters >50 m, frequently from purse seiners and trawlers, and the latter particularly inside the south Galician rías and close to vessels operating further offshore in Portuguese waters. Harbour porpoises were seen over the whole continental shelf, often next to beach seines, while long‐finned pilot whales and striped dolphins were mostly seen from vessels fishing offshore. Results suggest that cetacean occurrence is linked to prey distribution and that interactions with fisheries are most likely for common dolphins (with coastal purse seines and offshore trawls), bottlenose dolphins and harbour porpoises (coastal nets). The different data sources were complementary and provided results broadly consistent with previous studies on cetacean occurrence in the same area, although sightings frequency for some cetacean species was biased by survey method. Opportunistic sampling has certain restrictions concerning reliability, but can cover a wide area at comparatively low cost and make use of local ecological knowledge to yield information required for cetacean conservation. Copyright © 2014 John Wiley & Sons, Ltd.